Analisis Penerapan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada Laporan Keuangan Badan Usaha Milik Desa (BUMDes) Mekar Jaya Abadi Desa Sei-Limbat - Dinda Anggi Nurhayati; Saparuddin Siregar; Atika Atika (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2023)
BUMDes Mekar Jaya Abadi is a BUMDes in Langkat, located in Sei-Limbat village. BUMDes Mekar Jaya Abadi is an economic institution formed since 5 years and engaged in savings and loan business, trade, PPOB run by the village community. SAK ETAP is a standard created to be used in Financial Reporting published for many purposes for non-public organizations, that is, organizations without significant public responsibility. The purpose of this study is to explain the presentation of the Financial Statements of BUMDes Mekar Jaya Abadi, to compare the financial statements of BUMDes Mekar Jaya Abadi with SAK ETAP and also to explain whether the financial statements of BUMDes Mekar Jaya Abadi is in accordance with SAK ETAP. This study uses qualitative methods with descriptive approach. Sources of research data are primary data and secondary data. The results showed that the Financial Statements of village-owned enterprises (BUMDes) Mekar Jaya Abadi sei-Limbat village has not implemented SAK ETAP. Accounting practices in BUMDes referring to SAK ETAP (2013) have not been implemented due to lack of knowledge of BUMDes management regarding SAK ETAP. BUMDes Mekar Jaya Abadi desa Sei-Limbat only presents the balance sheet and Income Statement. And in each financial statement does not present the minimum items as stipulated in SAK ETAP.